Assessment of potential mobility of selected micropollutants in agricultural soils of the Czech Republic using their sorption predicted from soil properties - Kodešová, Radka; Fedorova, Ganna; Kodeš, Vít; Kočárek, Martin; Rieznyk, Oleksandra; Fér, Miroslav; Švecová, Helena; Klement, Aleš; Bořík, Adam; Nikodem, Antonín; Grabic, Roman (The Science of the total environment, 2023)
The sorption of organic contaminants in soils and sediment is a crucial factor affecting their mobility in the vadose zone environment. The Freundlich sorption isotherms were evaluated for eleven micropollutants and eight soils. The highest Freundlich sorption coefficients, KF, were obtained for triclosan (324 ± 153 cm3/nμg1-1/ng-1) followed by sertraline (120 ± 74), venlafaxine (74.3 ± 41.2), telmisartan (33.3 ± 13.6), atorvastatin (8.66 ± 4.78), bisphenol S (8.03 ± 4.87), lamotrigine (6.92 ± 3.02), 2-phenylbenzimidazole-5-sulfonic acid (3.77 ± 2.25), memantine (3.42 ± 1.64), 1-methyl-1H-benzotriazole (2.05 ± 0.99), and valsartan (0.88 ± 0.89). The KF values for the individual compounds were correlated with soil properties. Multiple linear regressions were used to derive equations for predicting the KF values using the soil properties. The first set of equations contained mainly properties with the strongest correlations with the KF values, e.g., a base cation saturation for positively charged compounds or a hydrolytic acidity for negatively charged compounds. The second set of equations contained properties included in the map of agricultural soils of the Czech Republic. These equations always indicated positive correlations with oxidizable organic carbon and clay content. They also included either a negative or positive correlation with pHKCl. A positive correlation with pHKCl was obtained for venlafaxine, memantine, and sertraline, which were mostly positively charged. A negative correlation with pHKCl was obtained for the remaining compounds. The second set of equations, the soil map, and the database of soil properties were used to predict the KF value distributions within the Czech agricultural soils. It resulted in similar KF distributions' patterns for valsartan, lamotrigine, atorvastatin, and telmisartan (with a positive correlation between KF and hydrolytic acidity), which considerably differed from the KF patterns for the other compounds. These maps were used to delineate areas with a leaching potential of the compounds toward groundwater that will serve as a tool for assessing a potential groundwater vulnerability.
Keywords: Corrosion inhibitors; UV filters; Pharmaceuticals; Sorption isotherms; Antiseptic; Soil types